2023
DOI: 10.1161/circulationaha.122.060799
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Lymphangiogenesis in Transplant Arteriosclerosis

Abstract: BACKGROUND: Transplant arteriosclerosis is a major complication in long-term survivors of heart transplantation. Increased lymph flow from donor heart to host lymph nodes has been reported to play a role in transplant arteriosclerosis, but how lymphangiogenesis affects this process is unknown. METHODS: Vascular allografts were transplanted among various combinations of mice, including wild-type, Lyve1 -CreER … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Lymphatics have been shown to be present in the adventitia of great vessels, but their function is not clear yet. Arterial lymphatics are widely believed to be beneficial in atherosclerosis by clearing cholesterol and immune cells from atherosclerotic plaques, but a new study recently showed that arterial lymphatics are one of the factors contributing to the development of transplant arteriosclerosis and that the inhibition of lymphangiogenesis would possibly prevent transplant arteriosclerosis by inhibiting the immune response [34][35][36][37][43][44][45]. Despite the fact that arterial lymphatics have been investigated in various diseases [38][39][40], a detailed characterization of the lymphatic vasculature within the arterial wall has not been carried out to date.…”
Section: Discussionmentioning
confidence: 99%
“…Lymphatics have been shown to be present in the adventitia of great vessels, but their function is not clear yet. Arterial lymphatics are widely believed to be beneficial in atherosclerosis by clearing cholesterol and immune cells from atherosclerotic plaques, but a new study recently showed that arterial lymphatics are one of the factors contributing to the development of transplant arteriosclerosis and that the inhibition of lymphangiogenesis would possibly prevent transplant arteriosclerosis by inhibiting the immune response [34][35][36][37][43][44][45]. Despite the fact that arterial lymphatics have been investigated in various diseases [38][39][40], a detailed characterization of the lymphatic vasculature within the arterial wall has not been carried out to date.…”
Section: Discussionmentioning
confidence: 99%
“…80,81 Vascular remodeling in allografts is known to result from immunologic rejection, which implicates the lymphatic system owing to its crucial role in the alloimmune response (immune response to nonself antigens). 82 During transplantation, donor lymphatic vessels are not anastomosed to that of the recipient. 83 Instead, the inflamed environment activates donor passenger leukocytes, which migrate out of the graft via the severed ends of donor lymphatic vessels and are taken up by the lymphatic capillaries of the recipient to be trafficked to the lymph nodes.…”
Section: Hf and Heart Transplantationmentioning
confidence: 99%
“…Both control and ischemia tissues were fully digested. The cell pellet was suspended in PBS and were subjected to single cell RNA sequencing as described previously [15,16]. A total of 63,645 cells remained post-filtering and data were normalized by "LogNormalize".…”
Section: Single-cell Rna Sequencing and Data Analysesmentioning
confidence: 99%